(untitled) - Ferrell, O. C. (Chicago, 1996)
This text emphasizes the nature of business and the trends that should change how business is conducted in the 21st century. Topics covered include: global, quality, diversity, productivity.
Keywords: Management,Quản trị; United States,Mỹ